2008
DOI: 10.1099/vir.0.83558-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the mechanism of antibody-dependent enhancement of feline infectious peritonitis virus infection: aminopeptidase N is not important and a process of acidification of the endosome is necessary

Abstract: Infection of the monocyte/macrophage lineage with feline infectious peritonitis virus (FIPV) is enhanced in the presence of anti-FIPV antibodies (antibody-dependent enhancement or ADE). We investigated the following unclear points concerning ADE of FIPV infection: (i) involvement of the virus receptor, feline aminopeptidase N (fAPN), in ADE activity in FIPV infection; (ii) necessity of acidification of the endosome in cellular invasion of FIPV. Virus receptor-blocking experiments using anti-fAPN antibodies at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…Using an IFA-based time of addition study involving a single replication cycle we were able to further clarify of the effect of time of addition, and refine the possible stage of the viral life cycle targeted by each compound. Based on the IFA results chloroquine was effective only if present at the time of infection, supporting the hypothesis that chloroquine acts during cell entry for FCoV FIPV1146, possibly through inhibition of endosomal pH (Takano et al, 2008). Hexamethylene amiloride and mefloquine provided significant antiviral effects when compound addition was delayed for up to 1 and 5 hpi respectively, suggesting that if the antiviral effects of these compounds arise through perturbation of endosomal function, the effects occur at different stages of the viral life cycle.…”
Section: Discussionsupporting
confidence: 52%
“…Using an IFA-based time of addition study involving a single replication cycle we were able to further clarify of the effect of time of addition, and refine the possible stage of the viral life cycle targeted by each compound. Based on the IFA results chloroquine was effective only if present at the time of infection, supporting the hypothesis that chloroquine acts during cell entry for FCoV FIPV1146, possibly through inhibition of endosomal pH (Takano et al, 2008). Hexamethylene amiloride and mefloquine provided significant antiviral effects when compound addition was delayed for up to 1 and 5 hpi respectively, suggesting that if the antiviral effects of these compounds arise through perturbation of endosomal function, the effects occur at different stages of the viral life cycle.…”
Section: Discussionsupporting
confidence: 52%
“…In this scenario, virusinfected macrophages overproduce B-cell differentiation/survival factors, which in turn act to promote B-cell differentiation into plasma cells. This same group 235 also investigated key steps in ADE in FIP such as involvement of the virus receptor and the requirement for acidification of the endosome for cellular invasion. They concluded that aminiopeptidatse N was not required for antibody enhancement.…”
Section: Infection and Immunitymentioning
confidence: 99%
“…Similarly, TGEV binds to porcine APN (Weingartl and Derbyshire, 1994), and has been shown to enter MDCK cells over-expressing porcine APN via endocytosis and acidification of the intracellular compartment facilitated membrane fusion (Hansen et al, 1998). FIPV also requires acidification of endosomes for successful entry (Takano et al, 2008). Inhibition of FIPV infection with nystatin, a pharmacological reagent that causes caveolae to flatten and disrupt the coat structure, and dynamin 2 inhibitor suggests that FIPV entry might actually involve some types of caveolae-dependent endocytosis (Van Hamme et al, 2008).…”
Section: Introductionmentioning
confidence: 99%